Inovasi Strategi Pembelajaran Kitab Kuning MI. Mambaul Ulum I Bata-Bata Pamekasan - Moh Badri; Ahmadi Ahmadi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
The background of the research was complex problems. It took a long time to learn the yellow book, so there was a need for a rapid program (acceleration) for learning the yellow book. The formulation of the problem of this thesis, First, how to learn the yellow book. Second, how to innovate the yellow book learning strategy. Third, the factors that inhibit and support yellow book learning. This research described the Innovation of the Yellow Book Learning Strategy of the Yellow Book Reading Acceleration Program in Class IV-VI MI. Mambaul Ulum I Bata-Bata.This study uses a qualitative approach and descriptive type, research that seeks to describe certain events with qualitative data. The data analysis in this study, namely the interactive model, through interviews, observation and documentation. The results of the research can be concluded that the yellow book learning in Class IV-VI MI. Mambaul Ulum I Bata-Bata, implemented. First, curriculum structure development (time allocation, learning resources, learning media, teacher selection Second, learning strategy selection (a) Complete Learning Strategy (b) Active Student Learning Method (c) Student activity-oriented learning (d) Expository (e) inquiry) Third, Obstacles in the implementation of the yellow book learning (a) It was difficult to create a fun learning atmosphere for the early age factor. (b) Bored feeling in studying the yellow book (c) Differences in individual quality levels (d) Conflict of duties between madrasah and Islamic boarding schools for students who were Muslim students. (e) Not at home for students.Â Penelitian dilatar belakangi masalah rumit dan membutuhkan waktu yang lama belajar kitab kuning, sehingga diperlukan adanya program cepat (Akslerasi) pembelajaran kitab kuning. Rumusan masalah tesis ini, Pertama, Bagaimana pembelajaran kitab kuning. Kedua, Bagaimana Inovasi strategi pembelajaran kitab kuning Ketiga, Faktor yang menjadi penghambat dan pendukung pembelajaran kitab kuning. Penelitian ini untuk mendeskripsikan Inovasi Strategi Pembelajaran Kitab Kuning Studi Tentang Program Akslerasi Baca Kitab Kuning di Kelas IV-VI MI. Mambaul Ulum I Bata-Bata. Penelitian ini menggunakan pendekatan kualitatif dan jenis deskriptif, penelitian yang berusaha mendeskripsikan kejadian tertentu dengan data yang bersifat kualitatif. Adapun analisis data dalam penelitian ini, yaitu model interaktif, melalui wawancara, observasi dan dokementasi. Hasil penelitian dapat disimpulkan pembelajaran kitab kuning di Kelas IV-VI MI. Mambaul Ulum I Bata-Bata, dilaksanakan. Pertama, Pengembangan struktur kurikulum (alokasi waktu, Sumber belajar, media pembelajaran, pemilihan guru Kedua, Pemilihan strategi pembelajaran (a) Strategi Belajar Tuntas (b) Cara Belajara Siswa Aktif (c) Pembelajaran berorientasi aktivitasÂ Peserta didik (d) Ekspositori (e) ingkuiri) Ketiga, Kendala dalam pelaksanaan pembelajaran kitab kuning (a) Sulit menciptakan suasana pembelajaran menyenangkanÂ faktor usia dini. (b) Bosan dan jenuh dalam mmpelajari kitab kuning (c) Perbedaan tingkat kualitas individu (d) Benturan tugas madrasah dan pondok pesantren bagi siswa yang berstatus santri. (e) Tidak kerasan bagi siswa yang berstatus santri.